Health sciences faculty usage behaviour of electronic resources and their information literacy practices. Issue 1 (7th February 2018) - Tandi Lwoga, Edda; Sukums, Felix
Abstract : Purpose: This paper aims to assess the usage behaviour of electronic resources (e-resources) among health sciences faculty and their level information literacy (IL) practices, and whether individual characteristics and IL skills can influence faculty member's usage of e-resources at Muhimbili University of Health and Allied Sciences (MUHAS). Design/methodology/approach: The authors conducted questionnaire surveys using a stratified random sampling technique to 135 faculty members at MUHAS between August and October 2016. The study used regression analysis to determine factors associated with the use of e-resources among faculty members at MUHAS. Findings: In addition to Google search engine, Wikipedia and four scholarly databases and search engines, the level of awareness of other 19 scholarly databases and search engines which are either subscribed or open access resources was less than 50 per cent. In addition to Google search engine, Wikipedia and five scholarly databases and search engines, the self-reported usage of other 18 scholarly databases and search engines was less than 50 per cent on the on "daily" and "weekly" categories. In total, 18 of the 32 IL competencies were rated below 50 per cent in the "good" grade by the faculty members. These IL competencies included information search techniques, reference management, critical appraisal and Web 2.0 technologies. The IL competencies ( ß = 0.223), an experience of using e-resources ( ß = 0.222) and some research disciplines [nursing ( ß = 0.191) and pharmacy ( ß = 0.186)] positively predicted self-reported usage of e-resources among faculty members. Originality/value: This is a comprehensive study that assesses the use patterns of e-resources across different health sciences disciplines in a university setting, and the influence of demographic characteristics and IL skills on the usage of e-resources in Tanzania. The results of this study will be useful to academic libraries to inform and review their policies and practices in relation to the IL training programmes and information services in a university setting.